2018
DOI: 10.1080/14719037.2018.1438501
|View full text |Cite
|
Sign up to set email alerts
|

Interaction styles of street-level workers and motivation of clients: a new instrument to assess discretion-as-used in the case of activation of jobseekers

Abstract: This paper proposes a re-conceptualization and a measurement instrument for street-level workers' interaction styles. Interaction styles are a relevant lens giving insight into how discretion is used and how street-level behaviour affects clients' motivation and engagement. The re-conceptualization builds on a revision of May and Winter's interaction style concept from the perspective of the psychological self-determination theory. Data from 349 caseworkers of the Flemish employment service were collected via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…On the one hand, the legal dimension can stimulate citizens' obedience with sanctions (May andWinter, 1999, 2000;Van Parys and Struyven, 2018) because it, among others, signals predictability (Liu et al, 2018). There is, indeed, some empirical support in the classic compliance literature.…”
Section: Conceptualizing Enforcement Stylementioning
confidence: 99%
“…On the one hand, the legal dimension can stimulate citizens' obedience with sanctions (May andWinter, 1999, 2000;Van Parys and Struyven, 2018) because it, among others, signals predictability (Liu et al, 2018). There is, indeed, some empirical support in the classic compliance literature.…”
Section: Conceptualizing Enforcement Stylementioning
confidence: 99%
“…As such, our research adds to the extant literature on SLBs’ discretion (Lipsky, 1980) alienation (Tummers et al, 2009) and divergence (Gofen, 2013). It also turns the spotlight away from the dysfunctional aspects of street-level bureaucracy alienation most addressed in the literature (Van Parys & Struyven, 2018), and toward the question of how policy alienation among SLBs can lead to functional behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that caseworkers, like other front-line workers (Lipsky, 1980;Maynard-Moody & Musheno, 2003), have different perspectives on their work and clients, which, in turn, affects their decisions made (Eikenaar, Rijk, & Meershoek, 2016;McDonald & Marston, 2008;Solvang, 2017;Van Parys & Struyven, 2018). For example, Solvang (2017) distinguished two perspectives on activation: "needs-orientation" and "employability enhancement."…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the different perspectives of caseworkers informs us about their drivers and what they want to improve in their clients, but this provides no information into how they try to achieve this. Indeed, various studies call for more research on these interactions to better understand how street-level bureaucrats use their discretion in practice (Hupe & Buffat, 2014;Van Parys & Struyven, 2018;Winter, 1999). Sainsbury (2008) explained that frontline workers, such as caseworkers, have to combine and reconcile supportive and coercive elements in their interaction with clients (Sainsbury, 2008), but this distinction remains very coarse and provides no insight into how this is translated in practice.…”
Section: Introductionmentioning
confidence: 99%